Mobile data warehouse architecture for portable paddy management system - Abu Bakar, Muhamad Shahbani; Ta'a, Azman; Muhamad Ridwan, Muhamad Ashraf (2013)
Business intelligence has been adopted for increasing profit and sharing information, especially for large sectors.One of the sectors is agriculture, which paddy is one of the biggest plantations for staple food industries.In particular, the Malaysian Paddy Management System (PMS) that provides the information to the farmers, brokers, agencies and government still lack of reliable and accurate information for planning and supporting decision making.Therefore, the data warehouse is used to integrate various agency databases into one big database for PMS.Moreover, the PMS will be implemented i n a mobile environment to ensure the paddy sector activity can be benefited from the information provided.The mobile data warehouse architecture is developed and uses the paddy farming in Kedah state as a case study.The portable PMS is developed based on mobile data warehouse architecture.The PMS is evaluated by using an expert review technique, which is focusing on the eight dimensions of the software quality model.